A Zero‐Power Optical, ppt‐ to ppm‐Level Toxic Gas and Vapor Sensor with Image, Text, and Analytical Capabilities. Issue 5 (7th April 2020) - Prévôt, Marianne Estelle; Nemati, Ahlam; Cull, Tobias Richard; Hegmann, Elda; Hegmann, Torsten
Abstract: Exposure to hazardous chemicals in the air humans breathe voluntarily or during dangerous situations such as fires or military conflicts (i.e., accidental or intentional) is a terrifying certainty. Technical challenges such as low cost, operational simplicity, response time, sensitivity, specificity, and environmental robustness often create barriers to the development of real‐time chemical sensor systems that will be broadly useful to both the private sector and the government. A multi‐mode liquid crystal sensor platform is presented that requires zero power to operate and can, based simply on the device design, be used as acute ppt‐level and analytical ppm‐level (dose × time) sensors. Inkjet printing of nanoparticles with a reactive ligand shell that affects the anchoring of nematic liquid crystal molecules facilitates the creation of sensors devices that produces an unmistakable warning or image solely based on the transmission or reflection of light. Based on the printing resolution and device architecture, these sensor devices can detect multiple gases or vapors on the same device and be used for remote sensing. Abstract : A zero‐power, optical toxic gas and vapor sensor platform for wearable or remote applications gives a direct visual indication of dangerous levels of specific toxic gases and vapors. These sensors are the display, are extremely economical to manufacture, and serve as warnings for specific uses for firefighters, military personnel in conflict zones, or employees in chemical manufacturing and water purification plants.